The comparison of performance between Bank Islam and Maybank from 2005 until 2010 / Muhammad Yazid Iskandar Naini - Iskandar Naini, Muhammad Yazid (Faculty of Business and Management, 2012)
Islamic banking in Malaysia started around two decades ago. Since then it has played an important role in financing and contributing to different economics and social sectors in the country in compliance with the principles of Shariah rules in Islamic banking practices. Since there have been limited studies on the financial performance of Islamic banks in the country. The aim of this paper is to examine and analyze the Malaysian experience with Islamic banking (Bank Islam) compare with conventional banking (Maybank). The paper goes further with performance of both banking segment. However, this paper used the performance evaluation methodology by conducting the profitability and growth ratio tests. This paper found that the profitability and growing situation for both banks has increased and both have expanded their investment and activities and had played an important role in financing projects in Malaysia. Among other findings, these Banks Islam have a high return in the profitability ratio compare with Maybank during year 2007 until 2009 and as we know this is the year of the recession. In comparison with the two banks, the results showed that Bank Islam more profit than Maybank because of the return higher than Maybank because the percentage of profitability more than conventional banking (Maybank). For growth ratio, it had been started by drastic decreasing trend causes of many factor such as unstable economic situation, increasing of oil and commodity prices, financial instability and sub-prime crisis. Moreover, declining trend had been continues happened from 2007 until 2009 because of recession and financial crisis that had been facing by the whole world and all sector especially banking sector. All of the factor had been inhibited the growth of Bank Islam and Maybank. Until the year of 2010, the growth had been started to show increasing trend causes of improvement world economic situation.